"A girl's place is in the home": Spatial gendered scripts in narratives of girls who have left or been pushed out of home. Issue 2 (26th July 2019) - Peled, Einat; Komem, Michal
Abstract: Little is known about the unique gendered experiences of runaway and homeless girls. This feminist study approaches the body and movement of these girls as potential sites of social control. We explored whether and how social values and directives that view the home as the proper place for girls are reflected in the narratives of 17 Israeli girls who have left or been pushed out of their homes, based on a critical interpretive analysis. We found evidence of the impact of gendered social control mechanisms in three key experiences of the girls: (a) delaying leaving home, even when suffering within it; (b) maintaining normativity after leaving home; and (c) help and supervision in encounters with professionals. The discussion further explores the impact of gendered social scripts on the girls' experiences both before and after leaving home and on the way in which they are offered and receive professional help. We call on helping professionals to examine critically how hegemonic gendered discourses about domestic and public spaces shape the experiences of these girls and the helping relationship and use these understandings to improve the services offered to them.